Punicalagin Restricts Growth, Promotes Apoptosis, and Reduces Invasion in Human Gastric Cancer Cells - Ding-Ping Sun; Yih-Huei Uen; Nai-Wen Kang; Chun-Chao Chang; Yu-Feng Tian; Chia-Lang Fang; Kai-Yuan Lin (SAGE Publishing, 2024)
This research investigated the anticancer properties of punicalagin, a prominent bioactive polyphenol extracted from Punica granatum L, in human gastric cancer cell lines. Normal and gastric cancer cells were exposed to different doses of punicalagin for various durations. Punicalagin exhibited cytotoxic effects on gastric cancer cells in a dose- and time-dependent fashion, while sparing normal gastric epithelial cells. It is noteworthy that among the 3 gastric cancer cells, HGC-27 cells were more resistant to punicalagin than 23,132/87 and AGS cells. Furthermore, punicalagin triggered apoptosis in gastric cancer cells, evidenced by a rise in both early and late apoptotic cell percentages. Western blot analysis further revealed that punicalagin elevated the levels of activated caspase-3. Conversely, punicalagin curtailed cell invasion and reduced the expression of MMP-2, MMP-9, Snail, and Slug. From a mechanistic standpoint, Western blotting indicated that punicalagin might inhibit the Erk and NF-κB pathways, leading to apoptosis induction and the inhibition of cell invasion in gastric cancer cells. These results indicate that punicalagin promotes apoptosis and inhibits cell invasion in gastric cancer cells by activating caspase-3 and suppressing MMP-2, MMP-9, Snail, and Slug through the inhibition of the Erk and NF-κB pathways.